Thinking about Punishment across Space and Time - TONRY, MICHAEL (Kriminologijos studijos, 2014)
This short essay shows why the customary two-categories of punishment theories (retributive theories and consequentialist theories) should be increased to three to include a-normative theory and how that would aid understanding of differences in punishment thinking and policy over time and across space. Section I lays out conventional typologies of punishment theories and explains why a-normative theory should be added. Section II introduces the general literature on determinants of punishment policies and practices. Section III briefly discusses Eastern and Central Europe. Section IV illustrates how the normative and explanatory theories when combined enrich explanations and improve understanding.Keywords: punishment theories; punishment policies and practices; history of punishment institutions and practices; comparative analysis of punishment institutions and practices; Eastern and Central Europe